Pengembangan Electronic Document Management System (EDMS) Sebagai Alternatif Pengarsipan di Perguruan Tinggi - M. Miftakul Amin (IIB Darmajaya, 2010)
The purpose of this paper is to develop an electronic document management system (EDMS). With a system is expected to be an alternative in the management of electronic documents in the college environment. Writing this using qualitative research approach with observation, document analysis, and interviews for data collection process. The system used a web-based system that is expected to reach the users of the system at large. This system has the functionality to store, archive, and retrieve electronic documents. Keyword : electronic document